STAGES OF DIGITAL TRANSFORMATION OF HEALTHCARE: RESULTS AND PROSPECTS - Irina A. Krylova (Siberian Journal of Life Sciences and Agriculture)
The digitalization of healthcare has gone through a period of experimentation, systematization and the beginning of large-scale application in medicine. Modern medical care uses fundamentally new technologies and effectively solves the clinical, logistical and educational problems of the healthcare system, acts as a routine process and is in constant dynamic development, which requires timely assessment and summing up of threshold results.